A systematic review of nuclear energy and public acceptance—A detailed analysis of evolution, emerging trends, and future research potentials - Ephraim Bonah Agyekum; Bashar Tarawneh; Farhan Lafta Rashid; Pankaj Kumar; Flavio Odoi-Yorke; Hussein Togun; Wulfran Fendzi Mbasso; Vladimir Ivanovich Velkin (Energy Exploration & Exploitation)
The Fukushima nuclear catastrophe in 2011 had a significant effect on nuclear development worldwide. Despite the numerous studies that assessed nuclear acceptance in recent times, there is currently no study that provides a detailed bibliometric review on the available literature. Therefore, a bibliometric review of public acceptance and nuclear energy has been carried out to better understand their evolution, trends, and future research potentials. In the period under review (2000–2023), 263 documents were published, and a total of 659 researchers produced the literature with an annual growth rate of 7.9%. The factorial analysis revealed key themes; grouped into three clusters: technical operational aspects of nuclear energy (Cluster 1), safety and risk management (Cluster 2), and public policy and social issues (Cluster 3). The word cloud analysis identified common subjects of research such as nuclear safety, risk perception, and public trust, suggesting that further research is needed on societal concerns and effective communication strategies. Collaboration patterns revealed strong research linkages between China and the US, and a number of other internationally collaborative countries such as the UK, Germany, and Japan. Future studies should investigate prediction models for public perceptions of nuclear power and concentrate on comprehending the elements that affect public trust, especially in developing nations. Research on public-private partnerships, psychological aspects influencing attitudes, and the effectiveness of educational initiatives is also crucial. The policy recommendations highlights the need for open governance and broad public participation in decisions concerning nuclear energy to alleviate concerns on safety and environmental risks and therefore nurture public trust in nuclear power.